A Dual pH‐ and Light‐Responsive Spiropyran‐Based Surfactant: Investigations on Its Switching Behavior and Remote Control over Emulsion Stability. Issue 21 (23rd March 2022) - Reifarth, Martin; Bekir, Marek; Bapolisi, Alain M.; Titov, Evgenii; Nußhardt, Fabian; Nowaczyk, Julius; Grigoriev, Dmitry; Sharma, Anjali; Saalfrank, Peter; Santer, Svetlana; Hartlieb, Matthias; Böker, Alexander
Abstract: A cationic surfactant containing a spiropyran unit is prepared exhibiting a dual‐responsive adjustability of its surface‐active characteristics. The switching mechanism of the system relies on the reversible conversion of the non‐ionic spiropyran (SP) to a zwitterionic merocyanine (MC) and can be controlled by adjusting the pH value and via light, resulting in a pH‐dependent photoactivity: While the compound possesses a pronounced difference in surface activity between both forms under acidic conditions, this behavior is suppressed at a neutral pH level. The underlying switching processes are investigated in detail, and a thermodynamic explanation based on a combination of theoretical and experimental results is provided. This complex stimuli‐responsive behavior enables remote‐control of colloidal systems. To demonstrate its applicability, the surfactant is utilized for the pH‐dependent manipulation of oil‐in‐water emulsions. Abstract : A spiropyran‐based cationic surfactant is presented. Its architecture renders the molecule dual‐responsive, possessing thereby an unexpected switching behaviour: While photo‐stimulation influences the surface‐active behaviour of the compound under acidified conditions, no notable photo‐responsiveness is observed at pH‐values >6.5. This effect is demonstrated by manipulating the integrity of an oil‐in‐water emulsion.